1970
DOI: 10.1017/s0021859600020906
|View full text |Cite
|
Sign up to set email alerts
|

The influence of heavily fertilized grass on mineral metabolism of dairy cows

Abstract: Groups of lactating dairy cows were fed on grass which had received various amounts of nitrogen and potash fertilizers. In the early part of the season not only was the herbage concentration of calcium and phosphorus lower in grass which had received potash fertilizer but in addition the ' availability' of the calcium to cows was depressed. Grass which had received large amounts of nitrogen fertilizer had a comparatively low dry-matter content in the autumn. Cows fed such grass were in negative balance for cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

1970
1970
1995
1995

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
3
5
0
Order By: Relevance
“…In these experiments calcium concentration of the mixed herbage averaged 5-8 g/kg D.M. This value is close to those reported by Simpson (1964), Hemingway et al (1968), Adams (1973) and Whitehead, Jones & Barnes (1978), Heddle & Crooks (1967), Crawshaw (1970) and Mudd (1970).…”
Section: Calciumsupporting
confidence: 91%
See 3 more Smart Citations
“…In these experiments calcium concentration of the mixed herbage averaged 5-8 g/kg D.M. This value is close to those reported by Simpson (1964), Hemingway et al (1968), Adams (1973) and Whitehead, Jones & Barnes (1978), Heddle & Crooks (1967), Crawshaw (1970) and Mudd (1970).…”
Section: Calciumsupporting
confidence: 91%
“…Magnesium concentration of the mixed herbage averaged 1-7 g/kg D.M., similar to that found by Whitehead et al (1978). Mudd (1970) reported a lower value (1-5 g/kg D.M.) while other authors (Reith et al 1964;Heddle & Crooks, 1967;Crawshaw, 1970;Adams, 1973) found higher values ranging from 1-7 to 2-2 g/kg D.M.…”
Section: Magnesiumsupporting
confidence: 83%
See 2 more Smart Citations
“…All the cultivars can therefore meet the daily potassium requirements of beef and dairy cattle. The high potassium content of the cultivars IS not likely to cause any toxic effect since about 90 % of the potassium intake by cattle is usually excreted through the kidney (MuDD 1970).…”
Section: Potassiummentioning
confidence: 99%